Front Cover: Solar RRL 1∕2017. Issue 1 (January 2017) - Pruzan, Dennis S.; Caruso, Anna E.; Liu, Yijin; Lin, Yu; Beall, Carolyn; Repins, Ingrid; Toney, Michael F.; Scarpulla, Michael A.
Abstract : Despite large research efforts and the materials sharing similar crystalline and electronic structures, the open circuit voltages ( V oc ) of kesterite Cu2 ZnSn(S, Se)4 based solar cells have remained well below those of chalcopyrite Cu(In, Ga)Se2 based cells. Pruzan et al. (article no.1600024 ) use element‐specific transmission X‐ray microscopy tomography with resolution of <200 nm to characterize elemental fluctuations in >100 μm 3 volumes of Cu2 ZnSnSe4 . Anticorrelation in the concentrations of Cu and Zn is found on the scale of polycrystalline grains, proving that disorder exists on length scales much larger than point defects. These results yield unique insight into the origins of composition and thus the electronic structure inhomogeneity and V oc deficit in kesterite devices.